Case Report: Primary Peritonitis as the Onset of Pediatric Ménétrier's Disease - Ana Barrés-Fernández; Andrés Piolatti-Luna; José Rafael Bretón-Martínez; José Rafael Bretón-Martínez; Elena Crehuá-Gaudiza; Elena Crehuá-Gaudiza; Carmen Quiñones-Torrelo; Anaïs Moscardó-Navarro; Cristina Fuertes-Latasa; Cecilia Martínez-Costa; Cecilia Martínez-Costa (Frontiers Media S.A., 2021)
Introduction: Primary peritonitis (PP) and Ménétrier's Disease (MD) are both rare conditions among pediatric population. Although about 150 MD cases have been described in the scientific literature to date, its onset with a PP is an unusual condition.Case Presentation: We present a case of an 11-year-old boy who was admitted to our unit because of abdominal pain and distension. Complementary tests showed ascites, bilateral pleural effusion, leukocytosis, increased acute phase reactants and hypoproteinemia with hypoalbuminemia. Laparoscopy ruled out appendicitis or visceral perforations and exposed purulent peritoneal fluid, compatible with PP. Biochemical stool analysis showed increased clearance of alpha-1-antitrypsin, which was consistent with a protein-losing enteropathy. Gastroscopy findings were compatible with MD. The clinical course was favorable and he had no recurrence after 12 months of follow-up.Conclusion: PP can be the first clinical manifestation of pediatric MD. Knowledge of MD and its generally benign nature in children is important in order to avoid excessive testing and unnecessary treatment.